Maverick Movies New Line Cinema and the Transformation of American Film - Herbert, Daniel (University of California Press, 2024)
Maverick Movies tells the improbable story of New Line Cinema, a company that cut a remarkable path through the American film industry and movie culture. Founded in 1967 as an art film distributor, New Line made a small fortune running John Waters's Pink Flamingos at midnight screenings in the 1970s and found reliable returns with the Nightmare on Elm Street franchise in the 1980s. By 2001, the company competed with the major Hollywood studios and reached global box office success with the Lord of the Rings franchise. Blurring boundaries between high and low culture, between independent film and Hollywood, and between the margins and the mainstream, New Line Cinema epitomizes Hollywood's shift in focus from the mass audience fostered by the classic studios to the multitude of niche audiences sought today. "At long last, a top film scholar takes a deep dive into New Line Cinema's remarkable and most unlikely history. Mining a wealth of primary sources and trade press accounts, and with access to New Line's renegade founder Bob Shaye himself, Daniel Herbert deftly recounts the company's rags-to-riches saga and firmly situates New Line as one of the most important Hollywood studios in the past half century." - THOMAS SCHATZ, author of The Genius of the System: Hollywood Filmmaking in the Studio Era "Exhibiting the same archival dexterity he brought to Videoland, Herbert reconsiders how New Line's eclecticism both predicted and reflected broader changes in US film culture of the late twentieth century. This book will revitalize the field of distribution studies." - CAETLIN BENSON-ALLOTT, author of The Stuff of Spectatorship: Material Cultures of Film and Television "Focusing on New Line Cinema, an indie outfit rooted in 1960s college-campus film culture that in the 1990s briefly became the tail that wagged the dog at the WB, Herbert crafts a compelling road map of the volatile movie industry of postclassical Hollywood." - JON LEWIS, author of Road Trip to Nowhere: Hollywood Encounters the Counterculture